Nonoperative treatment in peptic ulcer perforations and review of the literatüre - Bozdağ, Ahmet; Gültürk, Barış; Aksu, Ali; Kutluer, Nizamettin; Bozan, Mehmet Bugra; Gündoğdu, Tamer; Boyuk, Abdullah (Kahramanmaras Sutcu Imam University, 2021)
Background: Peptic ulcer perforation is a complication of peptic ulcer disease frequently encountered in the emergency departments. Although there are many treatment options ranging from nonoperative treatment to wide resections, surgery is the first treatment option in peptic ulcer perforations. In this article, we aimed to present the feasibility of nonoperative treatment in appropriate and selected cases. Materials and Methods: The data of the patients who were not operated but provided with medical treatment in our clinic between January 2016 and July 2018 were evaluated retrospectively. Results: Three of the patients were male, one of them was female, and the mean age was 58 years (range, 35-79). On physical examination, there were no signs of acute abdomen, only tenderness was observed in the right upper quadrant and epigastric region. Standing direct abdominal radiography revealed free air under the diaphragm in three patients. The diagnosis was made with tomographic findings in one patient. No contrast agent extravasation was observed in any patient. The patients were examined intermittently by a specialist surgeon, oral intake was permitted on the 4th day of hospitalization, and they were discharged on the 7th day on average. Conclusion: Peptic ulcer perforation is a condition, which is still common and requires emergency surgery in case of acute abdomen development. Although the time elapsed after perforation is a factor affecting mortality and morbidity, nonoperative treatment is a method that can be successfully applied under strict physical examination and laboratory follow-up in appropriate and selected patients without diffuse peritonitis and extravasation on CT with water-soluble contrast agent.

Amaç: Peptik ülser perforasyonu acil servislerde sık karşılaşılan peptik ülser hastalığının bir komplikasyonudur. Peptik ülser perforasyonlarında non-operatif tedaviden geniş rezeksiyonlara kadar pek çok tedavi seçeneği olmasına rağmen ilk tedavi seçeneği cerrahidir. Bu makalede uygun ve seçilmiş olgularda non-operatif tedavinin uygulanabilirliğini sunmayı amaçladık. Gereç ve Yöntemler: Kliniğimizde Ocak 2016 – Temmuz 2018 tarihleri arasında cerrahi uygulanmayıp medikal tedavi edilen hastaların verileri retrospektif olarak değerlendirilmiştir. Bulgular: Hastaların üçü erkek biri kadın ve ortalama yaşları 58 (35-79) idi. Hastaların fizik muayenesinde akut karın bulguları yok sadece sağ üst kadranda ve epigastrik bölgede hassasiyet vardı. Üç hastada ayakta direkt karın grafisinde diyafragma altında serbest hava vardı. Bir hastada ise tanı tomografik bulgularla konuldu. Hiçbir hastada kontrast madde ekstravazasyonu görülmedi. Hastalar uzman bir cerrah tarafından aralıklı muayene edildi ve yatışının 4. Günü orali açılıp ortalama 7. günde hastalar taburcu edilmiştir. Sonuç: Peptik ülser perforasyonu halen sık karşılaşılan ve akut karın tablosu gelişmiş ise acil cerrahi gerektiren bir durumdur. Her ne kadar perforasyon sonrası geçen süre mortalite ve morbitideyi etkileyen bir faktör olsa da seçilmiş uygun vakalarda suda çözünen kontrast madde ile çekilen BT de ekstravazasyon yoksa ve yaygın peritonit halinin olmadığı, uygun ve seçilmiş hastalarda sıkı fizik muayene ve laboratuar takibi altında başarıyla uygulanabilir bir yöntemdir.
Peptik Ülser Perforasyonlarında Nonoperatif Tedavi ve Literatürün Gözden Geçirilmesi
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi